The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1097/hjh.0000000000003163
|View full text |Cite
|
Sign up to set email alerts
|

Association of depressive symptoms and hypertension prevalence, awareness, treatment and control among USA adults

Abstract: The aim of this study was to measure hypertension prevalence, awareness, treatment and control by depressive symptoms among USA adults.Method: Using the National Health and Nutrition Examination Survey data from 2007 to 2018 (n ¼ 28 532), depressive symptoms were categorized as 'none or minimum', 'mild', 'moderate' and 'moderately severe or severe' by the Patient Health Questionnaire. Hypertension was assessed by history, blood pressure measures and antihypertensive medication use. Adjusted prevalence rates an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Our study found a strong connection between depression and a heightened risk of hypertension, which increased alongside the severity of depression. These results support previous findings, reinforcing the notion that depression contributes to the likelihood of developing hypertension [ 17 ]. Plausible explanations for this association may be traced to the dysfunction of the hypothalamic-pituitary-adrenal (HPA) axis and heightened sympathetic activation observed in individuals manifesting depressive symptoms [ 49 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study found a strong connection between depression and a heightened risk of hypertension, which increased alongside the severity of depression. These results support previous findings, reinforcing the notion that depression contributes to the likelihood of developing hypertension [ 17 ]. Plausible explanations for this association may be traced to the dysfunction of the hypothalamic-pituitary-adrenal (HPA) axis and heightened sympathetic activation observed in individuals manifesting depressive symptoms [ 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition to inherent biological or genetic factors, factors such as job stress, financial limitations, stress from racial discrimination, depression, and anxiety can all play crucial roles in the development of cardiovascular diseases [ 47 ]. Psychological stress has been linked to an augmented susceptibility to hypertension, with research elucidating an elevated hypertension risk among individuals afflicted with depression [ 17 , 42 , 48 ]. Our study found a strong connection between depression and a heightened risk of hypertension, which increased alongside the severity of depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our 10-year longitudinal study affirms that depressive symptoms significantly magnify the impact of hypertension, diabetes, and arthritis on reducing the life expectancy of middle-aged and older people, and this impact becomes apparent within a decade. Depressive symptoms diminish middle-aged and older individuals’ emotional regulation ( 117 ) and resilience to stress ( 118 ), heightening the challenge of managing mood and blood pressure for those with hypertension ( 119 ). Patients with depressive symptoms often exhibit an imbalance in the autonomic nervous system, particularly an overactivation of the sympathetic nervous system ( 120 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dose–response association was observed for hypertension awareness and treatment – the percentage increased more among those with greater depressive symptom and were highest among those with moderate severe or severe depressive symptoms. Greater depressive symptoms were associated with great hypertension awareness and treatment but not with control [4].…”
mentioning
confidence: 87%